EFISIENSI PENURUNAN KADAR BOD DAN TSS DENGAN BAKTERI KULTUR EM4 PADA AIR LIMBAH RUMAH SAKIT DENGAN SISTEM AERASI - Eksa Agung Utomo; Nurhayati; Benjamin Lekatompessy (JURNAL TECHLINK, 2022)
Water is an important resource for human life and other living things, and is also a valuable capital investment. Water quality is a problem because of the large amount of waste generated by human activities. This waste includes things like wastewater from households, factories, and other activities. Therefore, an effective micro-organism-4 (em4) is needed to treat wastewater. The purpose of this study was to determine whether the use of EM4 can reduce the amount of pollutants in hospital waste. The research method used is a laboratory experimental method used to study the effect of the variables studied. Experiment using the formula . The results of this study show the effectiveness of pollution levels using EM4 culture with a time of 16 days with the highest efficiency value found on day 16 in each parameter. Treatment on day 0 shows BOD 20.035 mg/L until treatment on day 16 results in BOD value of 6.087 mg/L and the second repetition (Y2) treatment on day 0 shows BOD value of 20.022 mg/L until treatment on day 16 BOD value is 5.022mg/L. It shows that the mean (Mean) BOD decreased from the initial concentration of 20.029 at 0 days to 5.555 at 16 days treatment. On the 16th day the efficiency value of setting aside BOD levels is 72.3%, on day 0 the TSS result is 85 mg/L until the repetition (Y1) on the 16th day the BOD result becomes 28 mg.L and the second repetition (Y2) on day 0 TSS result 83 mg/L until repetition (Y2) on day 16 the result TSS value 26 mg/L. Then the mean value (Mean) of TSS decreased from the initial concentration of TSS value of 84 mg/L on treatment day 0 and became 27 mg/L. on 16 days of treatment while for TSS levels that is equal to 67.86%.